2021
DOI: 10.3343/alm.2021.41.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals for Thyroid-Associated Hormones and the Prevalence of Thyroid Diseases in the Chinese Population

Abstract: Background Thyroid diseases are highly prevalent worldwide, but their diagnosis remains a challenge. We established reference intervals (RIs) for thyroid-associated hormones and evaluated the prevalence of thyroid diseases in China. Methods After excluding outliers based on the results of ultrasound screening, thyroid antibody tests, and the Tukey method, the medical records of 20,303 euthyroid adults, who visited the Department of Health Care at Peking Union Medical Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
3
14
0
Order By: Relevance
“…Difference in the upper limits may be explained by the age composition of the population living at different altitudes in China, as in the case of the three regions of Tibet, where the proportion of people aged >65 years was only approximately 5% (32). Obvious discrepancies were observed for TSH, FT3, and FT4 levels between males and females, although the effect of sex on TSH level was not as remarkable as those on FT3 or FT4, which was consistent with previous studies (14,27,33,34). Thus, sexspecific RIs for FT4 and FT3, but not for TSH, were proposed in our study and results showed that both the upper and lower limits of RIs for FT3 and FT4 were higher in males than in females, which can be interpreted by the potential effect of sex hormones on the HPT axis (10,35).…”
Section: Discussionsupporting
confidence: 91%
“…Difference in the upper limits may be explained by the age composition of the population living at different altitudes in China, as in the case of the three regions of Tibet, where the proportion of people aged >65 years was only approximately 5% (32). Obvious discrepancies were observed for TSH, FT3, and FT4 levels between males and females, although the effect of sex on TSH level was not as remarkable as those on FT3 or FT4, which was consistent with previous studies (14,27,33,34). Thus, sexspecific RIs for FT4 and FT3, but not for TSH, were proposed in our study and results showed that both the upper and lower limits of RIs for FT3 and FT4 were higher in males than in females, which can be interpreted by the potential effect of sex hormones on the HPT axis (10,35).…”
Section: Discussionsupporting
confidence: 91%
“…FT3 significantly increased upon puberty and showed a significant sex-specific difference at which age, while FT4 remained constant throughout puberty (10). In China, the sex/geographic/assay-specific and gestation-specific RIs of thyroid hormones have been established in adult populations (22)(23)(24)(25), emphasizing the need for assay-specific RIs of thyroid hormones in Chinese pediatric populations to avoid false positive or negative results.…”
Section: Discussionmentioning
confidence: 99%
“…The sex-specific and gestation-specific RIs of thyroid hormones have been established in Chinese adult populations (22)(23)(24)(25). Therefore, the present study aimed to evaluate the distribution of thyroid hormones and to establish age-and sex-specific RIs for a Chinese pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies rarely used large sample of data of Chinese population to establish RIs. Besides, instead of developing RIs for a broad spectrum of clinical chemistry analytes, previous publications usually focused on a single analyte or specific health issue, such as thyroid-associated biomarkers or myocardial enzyme analytes [16,17]. Hence, our study could fill these gaps to some extent.…”
Section: Discussionmentioning
confidence: 99%